Perancangan Pencatatan Sistem Akuntansi Pada Toko Samsung Excellent Partner - Supriyanto Supriyanto; Mareta Frisilia (Universitas Internasional Batam, 2021)
Practical work carried out gives the intention of applying the theory that has been learned and then implemented in order to serve the community. This practical work is expected to design an applicable recording system. The object of practical work leads to Micro, Small and Medium Enterprises (MSME) in the city of Batam. MSMEs that do not have accurate records or still use manual accounting records. The Samsung Excellent Partner store has been around for 6 years having problems producing effective and efficient reports. Faced the problem become the report to be presented inaccurately so that decision making can go wrong. The first step is to conduct business location visits and interviews with responsible person in order to gather detailed information. The next step is programming the accounting recording system through the Microsoft Office Access program. The resulting system must be capable of and in accordance with the Samsung Excellent Partner store so that existing obstacles can be overcome. The system results contain data compliance, transaction filling forms and reliable reports. The accounting recording system readiness will be implemented in front of the Samsung Excellent Partner store. The system that has passed the implementation is expected to be able to be applied in business activities. All reports presented by the system can facilitate all steps in enriching the Samsung Excellent Partner store business.